Attention Deficit Hyperactivity Disorders and Classroom-Based Interventions: Evidence-Based Status, Effectiveness, and Moderators of Effects in Single-Case Design Research. (August 2019) - Harrison, Judith R.; Soares, Denise A.; Rudzinski, Stephen; Johnson, Rachel
Students with attention deficit hyperactivity disorder (ADHD) experience symptoms of inattention, impulsivity, and hyperactivity that often manifest as academic impairment. As such, teachers must select interventions to increase the probability of success for students with ADHD in their classes. Prior meta-analyses have evaluated school-based intervention effects; however, no systematic review meta-analysis has evaluated the effectiveness of interventions implemented in classrooms with students with ADHD. Additionally, classroom-based studies are frequently conducted through single-case design methodology, and recent advances in meta-analytic techniques provide the opportunity to explore intervention effectiveness as evaluated through quality research. Therefore, to inform selection of evidence-based interventions to be implemented in classroom settings, the current systematic review with meta-analysis of single-case design studies was conducted to evaluate intervention effectiveness, evidence-based status, and moderators of effects for four intervention types (behavioral, instructional, self-management, and environmental) when implemented with students with ADHD in classroom settings. The analysis included 27 articles published from 1971 to 2018. Overall and specific to each intervention type, the results indicate that classroom-based interventions for students with ADHD were moderately effective. Instructional and self-management interventions were deemed evidence based by What Works Clearinghouse standards and potentially evidence based by Council for Exceptional Children standards. Behavioral interventions were found to be potentially evidence based by Council for Exceptional Children criteria and were most effective when selected through functional behavior analysis and implemented by researchers in secondary settings. Instructional interventions were more effective when implemented in special education settings targeting academic outcomes. Implications for research and practice are discussed.